THE MEANING OF 'PUBLIC ACCOUNTANT' - Webster, Norman E. (The Accounting Review, 1944)
Abstract The article focuses on the meaning of public accountants. It has different meaning for different individuals. The author is of the opinion that since some of the work of a public accountant is affected with a public interest, a definition suitable for use in a statute may be needed. But the best of definitions necessarily have their limitations. They will indicate the name of a larger group of which the item defined is a part and they will indicate one or at most a few characteristics which help to differentiate this item from other items in the larger group. It may be interesting, and possibly useful, therefore, to explore the historical background of the term public accountant as reflected in the literature of accountancy in the U.S. The administration of first Certified Public Accountant law was placed with the Regents of the University of the State of New York. To make effective the provisions of the new law, the Regents created the Board of Examiners for Certified Public Accountants that was authorized by Section 2 of the Act.